2020
DOI: 10.3390/microorganisms8101468
|View full text |Cite
|
Sign up to set email alerts
|

SARS-CoV-2: From Structure to Pathology, Host Immune Response and Therapeutic Management

Abstract: Coronaviruses are large, enveloped viruses with a single-stranded RNA genome, infecting both humans and a wide range of wild and domestic animals. SARS-CoV-2, the agent of the COVID-19 pandemic, has 80% sequence homology with SARS-CoV-1 and 96–98% homology with coronaviruses isolated from bats. The spread of infection is favored by prolonged exposure to high densities of aerosols indoors. Current studies have shown that SARS-CoV-2 is much more stable than other coronaviruses and viral respiratory pathogens. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 124 publications
0
12
0
1
Order By: Relevance
“…ammation and Immune Response-Molecular Cross-Talk iral infections are sometimes responsible for concomitant intestinal and upper tory airway pathological manifestations, and cooling and conjunctivitis symptoms o possible [7,91]. Both coronaviruses causing SARS in humans, SARS-CoV-1 and CoV-2, share the ACE2 cellular receptor interaction with the spike glycoprotein as ns of cellular entry and are equally stable and infectious as aerosols [7]. uring the pandemic, what is surprising and has put health management in an ency condition are the extent of the symptoms, which can easily progressively n and become complicated, and the high contagiousness of SARS-CoV-2.…”
Section: Inflammation and Immune Response-molecular Cross-talkmentioning
confidence: 99%
See 2 more Smart Citations
“…ammation and Immune Response-Molecular Cross-Talk iral infections are sometimes responsible for concomitant intestinal and upper tory airway pathological manifestations, and cooling and conjunctivitis symptoms o possible [7,91]. Both coronaviruses causing SARS in humans, SARS-CoV-1 and CoV-2, share the ACE2 cellular receptor interaction with the spike glycoprotein as ns of cellular entry and are equally stable and infectious as aerosols [7]. uring the pandemic, what is surprising and has put health management in an ency condition are the extent of the symptoms, which can easily progressively n and become complicated, and the high contagiousness of SARS-CoV-2.…”
Section: Inflammation and Immune Response-molecular Cross-talkmentioning
confidence: 99%
“…Viral infections are sometimes responsible for concomitant intestinal and upper respiratory airway pathological manifestations, and cooling and conjunctivitis symptoms are also possible [7,91]. Both coronaviruses causing SARS in humans, SARS-CoV-1 and SARS-CoV-2, share the ACE2 cellular receptor interaction with the spike glycoprotein as a means of cellular entry and are equally stable and infectious as aerosols [7].…”
Section: Inflammation and Immune Response-molecular Cross-talkmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, it has been reported that humoral immune responses are similar to other virus infections, and are associated with specific IgM and IgG and synthesis. At the beginning of the infection, B cells elicit a response against the nucleocapsid protein, whereas antibodies against the spike protein are produced after about one week from the appearance of symptoms [11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…Main treatment options suggested against SARS-CoV-2 include chloroquine/hydroxychloroquine, favipiravir, remdesivir, lopinavir/ritonavir, umifenovir, steroids, cepharanthine, interferon, ivermectin, ribavirin, convalescent plasma, anticoagulants, mesenchymal stem cells and neutralizing antibodies, among others. However, there is an urgent need for effective rapid diagnostics, vaccines and therapeutics to detect, prevent, treat and contain SARS-CoV-2 [24, 25, 26].…”
Section: Discussionmentioning
confidence: 99%